Effects of a structured heart failure program on quality of life and frequency of hospital admission in Saudi Arabia - Alghalayini, Kamal W. (Saudi Med J, 2019)
OBJECTIVES: To compare the quality of life (QOL) and frequency of hospital admission (FHA) in the past 4 months between congestive heart failure (CHF) patients involved in a structured heart failure program (HFP) compared with waitlisted controls. METHODS: This study, employing an ex-post-facto comparative cross-sectional design, involved 80 patients with CHF (40 in the HFP and 40 controls). Those in the HFP had been enrolled for at least 4 months. Controls were waiting to be enrolled in the program. Participants completed a questionnaire assessing demographic, social/cultural, psychological, and CHF-related physical health characteristics, along with the primary dependent variables, QOL and FHA. Bivariate and multivariate analyses assessed differences between those in the HFP and controls. RESULTS: Congestive heart failure patients in the HFP were significantly less likely than the control group to score below the median on heart failure-specific QOL, controlling for other variables (OR=0.83, 95% CI: 0.82-0.95, p=0.007). Those in the HFP were also significantly less likely than controls to be hospitalized within the past 4 months (OR=0.78, 95% CI: 0.69-0.88, p<0.001). Multivariate analyses indicated that CHF patients in the HFP were 95% less likely than controls to be admitted to the hospital during that period, independent of other risk factors for hospital admission. CONCLUSION: Involvement by patients with CHF in a structured HFP at King Abdulaziz University in Jeddah, Kingdom of Saudi Arabia, is associated with significantly higher quality of life and lower likelihood of being hospitalized compared to CHF patients not involved.